Mass Transfer Coefficient Extraction of Oleoresin from Zodia Leaf (Evodia suaveolens) with Ethanol Solvent Using Ultrasonic Cleaner - Siswanti Siswanti; Ratri Saviatri; Jeremy Adi Pratama (Eksergi, 2022)
The Aedes sp mosquito is a vector of Dengue Hemorrhagic Fever (DHF) and chikungunya which are still commonly found in Indonesia. To control DHF, natural insecticides from plants can be used. Zodia plants (Evodia suaveolens) can be used as natural insecticides because they contain essential oils that mosquitoes do not like. To obtain oleoresin with optimal quality and quantity, extraction can be carried out using ultrasonic waves. To design an efficient extractor, mass transfer coefficient data is needed. Until now, the data is still difficult to obtain. The experiment was carried out using an ultrasonic cleaner, by observing the concentration of oleoresin for various leaf mass ratios of 4, 6, 8, 10, and 12 grams, extracted with 300 mL ethanol for 900 seconds. Concentration observations were also carried out for a time variation of 90 - 900 seconds, with 90 seconds intervals. The best extraction results were tested using GC-MS, to determine the components in the oleoresin. To determine the mass transfer coefficient (Kc) is to make a relationship between concentration and time for the best ratio of leaf weight and ethanol volume.Based on research that has been done with 300 mL of ethanol and extraction time of 900 seconds, the highest concentration was 0.0120 gr/mL, for the experiment using a leaf weight of 12 gr. The largest percentage (%) of oleoresin that could be extracted was 88.5%, for the experiment the leaf weight was 2 g. The optimum mass transfer coefficient (Kc) is 0.161088 1/minute. These data were obtained for the experiment of the relationship between concentration and time. Oleoresin from Zodia leaves contains 20.61% nerolidol. This compound has effectiveness as a mosquito repellent.